2009
DOI: 10.1111/j.1365-2427.2008.02136.x
|View full text |Cite
|
Sign up to set email alerts
|

Availability of and access to critical habitats in regulated rivers: effects of low‐head barriers on threatened lampreys

Abstract: 1. Conservation of freshwater animal populations requires their access to, as well as sufficient availability of, critical habitats, such as those for reproduction. Abundant smallscale barriers may cause extensive fragmentation of freshwater habitat but, by comparison to larger structures their effects are rarely considered by catchment managers. The relationship between the distribution of, and access to, spawning habitat in a regulated river, characterized by abundant small barriers, was examined for river l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
149
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(156 citation statements)
references
References 61 publications
5
149
0
2
Order By: Relevance
“…Impacts are invariably observed most rapidly and dramatically when watercourses are dammed, but the cumulative effects of large numbers of smaller obstructions can also be significant (Lucas et al 2009;Nunn et al 2008). Tools are available to mitigate the impacts of barriers, thereby facilitating the migration of fishes up-and downstream or into adjacent watercourses (Cowx 1998;FAO 2002;Larinier 1998Larinier , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Impacts are invariably observed most rapidly and dramatically when watercourses are dammed, but the cumulative effects of large numbers of smaller obstructions can also be significant (Lucas et al 2009;Nunn et al 2008). Tools are available to mitigate the impacts of barriers, thereby facilitating the migration of fishes up-and downstream or into adjacent watercourses (Cowx 1998;FAO 2002;Larinier 1998Larinier , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, 270 Lasne et al (2015) revealed that barrier removal can be the most effective mechanism to enable P. marinus passage, with higher numbers of nests that were more consistently distributed occurring several years after barrier removal in a French coastal stream. This con-275 trasts to Lucas et al (2009) who reported that in the River Derwent, England, only 2% of adult P. fluviatilis spawners were recorded in 98% of the river's total spawning habitat as this was located above a series of impassable low-head barriers.…”
Section: Physical Obstructionsmentioning
confidence: 99%
“…The blockage of migratory routes can thus significantly affect the lifetime fitness of P. marinus, impacting their population growth 230 and distribution, spawning success and recruitment, and affecting their vulnerability to fishing and predators (Andrade et al, 2007;Klamath River Expert Panel, 2010;Mateus et al, 2012). The passage of river lamprey Lampetra fluviatilis over 235 anthropogenic barriers has received some attention in Europe in recent years (Masters et al, 2006;Lucas et al, 2009;Kemp et al, 2011;Russon et al, 2011;Foulds and Lucas, 2013) and this literature might be informative for P. marinus, although some caution is suggested given the 240 larger body sizes of the latter. Elevated water flow increases their migratory activity (Masters et al, 2006) and this assists their passage through barriers that otherwise can be impassable at reduced flows (Lucas et al, 2009;Foulds and Lucas, 2013).…”
Section: Physical Obstructionsmentioning
confidence: 99%
See 2 more Smart Citations